2021
DOI: 10.1136/neurintsurg-2021-018241
|View full text |Cite
|
Sign up to set email alerts
|

Systematic CT perfusion acquisition in acute stroke increases vascular occlusion detection and thrombectomy rates

Abstract: BackgroundIn patients with stroke, current guidelines recommend non-invasive vascular imaging to identify intracranial vessel occlusions (VO) that may benefit from endovascular treatment (EVT). However, VO can be missed in CT angiography (CTA) readings. We aim to evaluate the impact of consistently including CT perfusion (CTP) in admission stroke imaging protocols.MethodsFrom April to October 2020 all patients admitted with a suspected acute ischemic stroke underwent urgent non-contrast CT, CTA and CTP and wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 15 publications
1
39
0
Order By: Relevance
“…The value of CTP-based screening might be higher for physicians with less experience in neuroimaging assessments. In this study we reported a wide variety of sensitivity differences as the current evidence comparing NCCT+CTA+CTP with NCCT+CTA based LVO detection is limited by a small sample size and suboptimal research designs (1)(2)(3)(4). Third, we used conservative ORs for the EVT treatment effect based on the MR CLEAN trial (12).…”
Section: Probabilistic Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The value of CTP-based screening might be higher for physicians with less experience in neuroimaging assessments. In this study we reported a wide variety of sensitivity differences as the current evidence comparing NCCT+CTA+CTP with NCCT+CTA based LVO detection is limited by a small sample size and suboptimal research designs (1)(2)(3)(4). Third, we used conservative ORs for the EVT treatment effect based on the MR CLEAN trial (12).…”
Section: Probabilistic Sensitivity Analysismentioning
confidence: 99%
“…Brain tissue perfusion maps derived from computed tomography perfusion (CTP) have been suggested to improve occlusion detection in acute ischemic stroke (AIS) patients if used in addition to CT angiography (CTA) and non-contrast CT (NCCT) (1)(2)(3)(4). Although CTP is primarily considered to select patients for endovascular treatment (EVT) (5), screening all suspected AIS patients presenting within six hours after symptom onset with CTP could also enhance the detection of patients with a large vessel occlusion (LVO) EVT; resulting in more patients who benefit from EVT and less missed occlusions (6).…”
Section: Introductionmentioning
confidence: 99%
“…An important finding of Olive-Gadea et al is that the likelihood of identifying a vessel occlusion on CTA alone was under 50% for hypoperfusion volumes (Tmax >6 s) less than 90 mL, whereas the probability of undergoing EVT in these patients was 88.4% 1. This is surprising, because given that the patient has such a high probability of undergoing EVT, one would expect a high likelihood of identifying a vessel occlusion on CTA.…”
mentioning
confidence: 97%
“…In their JNIS study, Olive-Gadea et al present a retrospective single-center study demonstrating that inclusion of systematic CT perfusion (CTP) in acute stroke imaging protocols improves the detection of intracranial vessel occlusions and helps to identify additional endovascular treatment (EVT) candidates compared with using CT angiography (CTA) alone 1. Their sample group consisted of 338 consecutive patients with suspected acute ischemic stroke who underwent urgent non-contrast CT, CTA, and CTP.…”
mentioning
confidence: 99%
See 1 more Smart Citation